1105. The Burden of Infections Prior to Chimeric Antigen Receptor (CAR) Modified T-cell Therapy Predicts Post-CAR T-cell Infectious Complications. (31st December 2020) - Garner, Will; Samanta, Palash; Dorritie, Kathleen; Sehgal, Alison; Winfield, Denise; Agha, Mounzer; Boudreau, Robert; Nguyen, Minh Hong T; Haidar, Ghady
Abstract: Background: CAR T -cell therapy (CTT) is a novel treatment for B-cell cancers. CTT patients (pt) are at risk of infection due to neutropenia, cytokine release syndrome (CRS), and CAR T-cell related encephalopathy syndrome (CRES), which are treated with steroids and tocilizumab (anti-IL-6). This is a single-center study evaluating the risk factors for infection after CTT. Methods: A retrospective review was conducted of 60 consecutive CTT recipients between 7/17/17 and 9/5/19. Data was collected from 6 months (mo) pre- and at least 6 mo post-CTT. Data was censored for death, additional chemotherapy, or loss to follow up. Cox proportional hazard and Poisson regression were used. Results: Median age was 66 (23-84) years; 48% (29) were female. The most common cancer was non-Hodgkin lymphoma (89%, 54). 25% (15) had a prior stem cell transplant (SCT). 73% (44) and 45% (27) of pts developed CRS and CRES, respectively. 43% (26) received steroids; 65% (39) received tocilizumab. In the 6 mo pre-CTT, 39 infections occurred in 45% (27) of pts. 103 infections occurred in 66% (40) after CTT; 33 (55%) had an infection within 6 mo. Infections were bacterial (52%; 54/103), viral (30%; 37/103), fungal (10%; 10/103), mycobacterial (1%; 1/103), protozoal (1%; 1/103). Cumulative incidence of infection in the first 6 mo are shown in Fig 1 . All-cause and infection-related mortality were 32% (19) and 15% (9), respectively. Mortality among pts with fungal infections was 20% (2/10). Infection density was 1.28 and 0.58 infections per 100 pt-days between days 0-30 and 30-89, respectively. Factors associated with infection post CTT were number (no.) of infections in the 6 mo prior to infusion (HR 1.62, CI [1.1-2.38]; p=0.015), no. of lines of therapy in the 6 mo pre-CTT (HR 1.52, CI [1.01-2.27]; p=0.04), prior allogeneic SCT (HR 5.96, CI [1.34-26.47]; p=0.019), and no. of tocilizumab doses. Grade 1 CRS and grade 2 CRES were risk factors between days 0-30 and 0-180, respectively (HR 4.67, CI [1.02 -21.4], p = 0.047; HR 2.48, CI [1.17-5.23], p = 0.02). Fig 1: Cumulative Incidence of Infection 6 Months Post CAR T-cell Therapy Conclusion: Infections after CTT are common. Infection before CTT was associated with risk of infection after CTT. Pt selection may ameliorate this risk. Mortality due to fungal infections was high. Randomized-controlled trials of antifungal prophylaxis in high-risk pts are needed. Disclosures: All Authors : No reported disclosures